2017
DOI: 10.1371/journal.pone.0178359
|View full text |Cite
|
Sign up to set email alerts
|

Positive mental health among health professionals working at a psychiatric hospital

Abstract: BackgroundPositive mental health (PMH) is a combination of emotional, psychological and social well-being that is necessary for an individual to be mentally healthy. The current study aims to examine the socio-demographic differences of PMH among mental health professionals and to explore the association between job satisfaction and total PMH.MethodsDoctors, nurses and allied health staff (n = 462) completed the online survey which included the multidimensional 47-item PMH instrument as well as a single item j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 59 publications
1
18
0
12
Order By: Relevance
“…The total PMH values observed in the overall study sample (4.68), and for the Chinese (4.18), Malay (4.96) and Tamil (4.92) versions, are higher than the original PMHI estimates generated in the general population (4.53) (Vaingankar et al, 2011), people with mental disorders (3.94) (Sambasivam et al, 2016) and working adults (4.54) (Picco et al, 2017). Low levels of PMH and well-being are expected in patient populations (Markowitz, 1998;Nicoletti et al, 2017;Ritsner et al, 2000) and can explain the difference in PMH from the current sample.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The total PMH values observed in the overall study sample (4.68), and for the Chinese (4.18), Malay (4.96) and Tamil (4.92) versions, are higher than the original PMHI estimates generated in the general population (4.53) (Vaingankar et al, 2011), people with mental disorders (3.94) (Sambasivam et al, 2016) and working adults (4.54) (Picco et al, 2017). Low levels of PMH and well-being are expected in patient populations (Markowitz, 1998;Nicoletti et al, 2017;Ritsner et al, 2000) and can explain the difference in PMH from the current sample.…”
Section: Discussionmentioning
confidence: 63%
“…The Positive Mental Health Instrument (PMHI), the initial English language version, was developed and validated as part of a national epidemiological study conducted in 2010 in Singapore (Vaingankar et al, 2011;Vaingankar et al, 2012). Since its first development, the instrument has been extensively used and studied in different populations such as communitybased general population samples (Vaingankar et al, 2011;Vaingankar et al, 2018), working adults (Picco et al, 2017), patients with mental illnesses (Vaingankar et al, 2016) and caregivers of older adults (Ong et al, 2018). It has consistently shown high reliability and demonstrated strong construct and criterion validity in English-literate samples.…”
Section: Introductionmentioning
confidence: 99%
“…Data relating to attitudes of mental health professionals were extracted from a study which aimed to explore associative stigma and positive mental health among staff working at the Institute of Mental Health (IMH), the only tertiary psychiatric service provider in Singapore [ 29 ]. This was a cross-sectional, online survey which used convenience sampling.…”
Section: Methodsmentioning
confidence: 99%
“…A study among nurses showed a negative correlation between perceived stress and happiness scores [ 13 ] which can help explain the increased social well-being seen amongst HCP in our study as their professional role may provide them with a large sense of satisfaction and meaning towards protecting the community from COVID-19 even though occupational stress level is likely higher. Job satisfaction was also observed to be significantly associated with a high level of total positive mental health status, and so was the workplace environment [ 35 ]. A review on impact of COVID-19 on mental health showed student status, unemployment, presence of chronic illness, poor self-rated health were some of the risk factors that predicted stress in the general community [ 14 ].…”
Section: Discussionmentioning
confidence: 99%